Emergências climáticas e educação matemática : habitando brechas das salas de aula de matemática - Dornelles, Deise Cristina Noronha (2023)
This work has as main goal to give a deep look into the process of implementing activities related to climate emergencies with Basic Education students. The main theoreticalmethodological reference is the Semantic Fields Model, proposed by Romulo Campos Lins (1999, 2012). Based on the implementation of activities in a Basic Education classroom, we carried out plausible readings of discussions, problematizations and student productions on themes, situations and activities that explain climate emergency scenarios. Our devises in data production were a field notebook, our readings of activities and presentations carried out by students, as well as photos, stories and discussions shared in the classroom. These activities were implemented in a mathematics classroom in the second year of high school in the state network of Mato Grosso. Our educational product is constituted as a documentary, produced from this process of implementing activities, as well as our dialogues, learning, (un)learning with students. This is material with the intention of inviting mathematics teachers to give a real attention to the importance and need of this emergency in our present times. One of the main considerations of this work is towards a discussion with students that goes beyond the contents and the building of schools, because it is still very much centered on the narrative of a school as a place for teaching and learning mathematical content. One point of this investigation is to “put on the table” a problem that crosses our lives and our possibility of existence: the climate emergencies. Another point is in relation to a mathematics teacher, who moves in an attempt to escape the narrative of improving students' content learning in Basic Education, in a process to fill gaps in a classroom, in activities that are related with scenarios involving climate emergencies.